Early-Life Mild Traumatic Brain Injury Alters Neurodevelopment and Behavior in Mice - Rachel R. Corrigan; Anna O. Lanier; Emily S. Dresher; Sahibjot Sran; Tracy A. Bedrosian (Neurotrauma Reports)
Approximately 280 children per 100,000 experience closed-head injuries each year, with over 80% being mild in severity. While most children with mild injuries do not require admission to a hospital and recover well over time, some children experience persistent behavioral and cognitive abnormalities that continue into adolescence. Mild traumatic brain injury (mTBI) during early life has potential to disrupt critical developmental processes and lead to long-term consequences; however, the mechanistic underpinnings of mTBI’s effects on brain development remain understudied. Here, we investigated the effects of early-life mTBI on developmental outcomes using a mouse model. Injury was induced on post-natal day 7 by a single weight drop of one of three different impact intensities. Injury resulted in significant white matter loss as measured by myelin basic protein immunoreactivity at 5 days post injury (dpi). There was no change in the extent of Iba1-positive microglial staining at 5 dpi; however, there was increased expression of complement signaling proteins responsible for microglial-regulated synaptic pruning during this time in development. To assess the neurological consequences of mTBI, we examined the development of innate behaviors and ultrasonic vocalization communication. Injured mice were slower to achieve developmental milestones and exhibited altered communication, indicating functional deficits associated with mild injury. Altogether, this study provides evidence for neurodevelopmental consequences of mTBI and demonstrates lasting behavioral effects, suggesting further investigation of mechanisms contributing to neurological effects of mild injury in early life is warranted.